2022
DOI: 10.3390/cells11182852
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Controlling MicroRNA Expression in Tumor

Abstract: MicroRNAs (miRNAs) are widely present in many organisms and regulate the expression of genes in various biological processes such as cell differentiation, metabolism, and development. Numerous studies have shown that miRNAs are abnormally expressed in tumor tissues and are closely associated with tumorigenesis. MiRNA-based cancer gene therapy has consistently shown promising anti-tumor effects and is recognized as a new field in cancer treatment. So far, some clinical trials involving the treatment of malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 167 publications
0
11
0
Order By: Relevance
“…In addition, miRNAs are involved in the regulation of pathophysiological processes, such as cell proliferation and differentiation, apoptosis, and oxidative stress. 23,24 To search for key miRNAs associated with cAKI, we examined the differences in renal miRNA expression profiles between control and cisplatin-induced mice using high-throughput sequencing. The results showed that miR-30e-5p was the key miRNA whose expression was downregulated in cAKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, miRNAs are involved in the regulation of pathophysiological processes, such as cell proliferation and differentiation, apoptosis, and oxidative stress. 23,24 To search for key miRNAs associated with cAKI, we examined the differences in renal miRNA expression profiles between control and cisplatin-induced mice using high-throughput sequencing. The results showed that miR-30e-5p was the key miRNA whose expression was downregulated in cAKI.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of life sciences, miRNAs play an increasing important role in disease progression. In addition, miRNAs are involved in the regulation of pathophysiological processes, such as cell proliferation and differentiation, apoptosis, and oxidative stress 23,24 . To search for key miRNAs associated with cAKI, we examined the differences in renal miRNA expression profiles between control and cisplatin‐induced mice using high‐throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are non-coding RNA molecules approximately 21–25 nucleotides long that target the 3′-untranslated region of specific genes and regulate several metabolic pathways by modulating gene transcription and translation 27 . miRNAs can regulate tumor incidence and development by controlling tumor cell growth, invasion, migration, and chemotherapeutic resistance 28 . miR-122-5p is involved in regulating the development of several malignant tumors such as gastric cancer, renal cell carcinoma, liver cancer, melanoma, and breast cancer 29 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbas et al [16] introduced the idea of using mixed adhesive joints to increase joint strength and minimize peak adhesive stresses. Chen et al [17] numerically analyzed the strength of adhesive bonded joints under the effect of graded substrates. Marques et al [18] and Durodola et al [19] used Functionally graded adhesive joints.…”
Section: Introductionmentioning
confidence: 99%